Prosthetic valve endocarditis. A survey. Issue 1 (July 1987) - Ben Ismail, M; Hannachi, N; Abid, F; Kaabar, Z; Rougé, J F
Abstract : Fifty eight patients (aged 8-59 years, mean 27) treated for prosthetic valve endocarditis from January 1966 to January 1985 were studied retrospectively by review of case notes. There were 12 cases of early and 46 cases of late prosthetic valve endocarditis. These developed in 28 patients with an isolated aortic valve, in 26 with an isolated mitral valve, and in four with both aortic and mitral prosthetic valves. Streptococci were the most commonly isolated microorganisms, followed by staphylococci, Gram negative bacteria, and fungi. A surgical (34 cases) or a necropsy specimen (10 cases) from 44 cases was examined. Eighty two per cent of the patients had congestive heart failure. Twenty four of the 58 patients were medically treated and 17 died (70% mortality). Combined medical and surgical treatment was used in 34 patients; the main indication for surgery was congestive heart failure. Fourteen patients on combined treatment died (40% mortality). Persistent sepsis and prosthetic valve dehiscence were the most common early and late operative complications. The most important influences on outcome were congestive heart failure, the type of micro-organism, the severity and extent of anatomical lesions, the time of onset of prosthetic valve endocarditis, and the type of treatment. This survey indicates that only patients without congestive heart failure or embolic complications and with sensitive micro-organism should be treated medically. In view of the poor prognosis patients with prosthetic valve endocarditis associated with congestive heart failure, persistent sepsis, and repeat arterial emboli should be treated by early surgical intervention.